Incidence of neuropathic pain after endodontic treatment - Aliberas, Jordi Tomás (2024)
Objectives: To determine the incidence of neuropathic pain after endodontic treatment with follow-up at 6 months. Materials and Methods: This was a prospective observational clinical study that was carried out on patients who underwent endodontic treatment or retreatment carried out in the Master of Endodontics at the International University of Catalonia (UIC) from January 2022 to December 2022. After the treatment, a six-month follow-up was carried out, determining the presence of persistent pain, and whether the cause was of non-odontogenic origin, through anamnesis and physical examination carried out in the Department of Craniomandibular Dysfunction and Orofacial Pain of the Faculty of Dentistry. Results: A total of 231 treatments were obtained, obtaining a 53% response via telephone call. A descriptive analysis of the results was done, there were 88 patients who did not present pain after 6 months of endodontic treatment (72%); while 35 patients reported pain (28%). 9% of the cases with pain were caused by endodontic failure, in 74% the cause was due to involvement of another tooth and 11% due to periodontal reasons. It was estimated that 1.5% of treated patients had failed endodontic treatments at 6 months of follow-up. The causes of persistent pain were periodontal problems, such as food packaging, dentin hypersensitivity or pulpal origin associated with another tooth. Conclusions: After 6 months of follow-up, no patient presented neuropathic origin pain.